Przerwane śniadanie z Braćmi Mongolfier - Hendrykowski, Marek (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2015)
The Montgolfier Brothers’ Interrupted Breakfast Marek Hendrykowski’s study presents an analysis of a unique film made in 1979 by the young Polish director Michał Tarkowski during his studies in the Lodz Film School. The author argues that in several respects Tarkowski’s The Montgolfier Brothers’ Interrupted Breakfast is a perfect example illustrating the original use of art-cinema conventions and forms for what might be interpreted as the aesthetics of camp, but also as mediated “landscape of events” (based on a term invented by Paul Virilio).